E. coli contamination in hot springs at Hulu Selangor/ Muhamad Nur Fitri Abd Rahim... [et al.] - Abd Rahim, Muhamad Nur Fitri; Mohd Shahid, Nadiatul Syima; Masgnut, Mohd Izwan; Ismail, Rodziah; Mohd Yatim, Siti Rohana; Rajan, Shantakumari (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Recreational use of water can have benefits to health and well-being. However it also poses a risk to health through exposure to chemical and microbiological organisms as well as physical risks such as drowning and injury if the water is polluted and unsafe. There are many well-known hot springs in Malaysia that are serves as tourist attractions. The purpose of this study was to assess the recreational water quality at selected hot springs in Hulu Selangor. A total of three samples of water were taken from each of the three hot springs in Hulu Selangor which are Kuala Kubu Bharu, Batang Kali and Kerling. The study was repeated twice. Physical parameters (pH, temperature and turbidity) were measured in-situ using Hanna Multiparameter and turbidity meter. Biological parameter (E. coli) was measured ex-situ used colilert method. All physical parameters for all three hot springs complied with the standard but the number of E. coli exceeded the acceptable level from the standard in all of the hot springs. An independent t-test showedthat there was a significant difference (p<0.05) for turbidity during high peak day and low peak day between hot springs but there are no significant difference for pH, temperature and E. coli. There are no significant correlation (p>0.05) between the presence of the E. coli with turbidity. The findings in this study shows that increased users may pollutethehot spring and posea risk to the users. Thus, this study can be used to formulate strategies to overcome the issues.